Disordered Peptides Looking for Their Native Environment: Structural Basis of CB1 Endocannabinoid Receptor Binding to Pepcans - Emendato, Alessandro; Guerrini, Remo; Marzola, Erika; Wienk, Hans; Boelens, Rolf; Leone, Serena; Picone, Delia (Frontiers in Molecular Biosciences, 2018)
Endocannabinoid peptides, or “pepcans”, are endogenous ligands of the CB1 cannabinoid receptor. Depending on their length, they display diverse activity: For instance, the nona-peptide Pepcan-9, also known as hemopressin, is a powerful inhibitor of CB1, whereas the longer variant Pepcan-12, which extends by only three amino acid residues at the N-terminus, acts on both CB1 and CB2 as an allosteric modulator, although with diverse effects. Despite active research on their pharmacological applications, very little is known about structure-activity relationships of pepcans. Different structures have been proposed for the nonapeptide, which has also been reported to form fibrillar aggregates. This might have affected, the outcome and reproducibility of bioactivity studies. In an attempt of elucidating the determinants of both biological activity and aggregation propensity of Pepcan-9 and Pepcan-12, we have performed their structure characterization in solvent systems characterized by different polarity and pH. We have found that, while disordered in aqueous environment, both peptides display helical structure in less polar environment, mimicking the proteic receptor milieu. In the case of Pepcan-9, this structure is fully consistent with the observed modulation of the CB1. For Pepcan-12, whose allosteric binding site is still unknown, the presented structure is compatible with the binding at one of the previously proposed allosteric sites on CB1. These findings open the way to structure-driven design of selective peptide modulators of CB1.